2020
DOI: 10.1186/s13561-020-00295-8
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and validity assessment of methods used in discrete choice experiments of primary healthcare professionals

Abstract: Introduction Discrete choice experiments (DCEs) have been used to measure patient and healthcare professionals preferences in a range of settings internationally. Using DCEs in primary care is valuable for determining how to improve rational shared decision making. The purpose of this systematic review is to assess the validity of the methods used for DCEs assessing the decision making of healthcare professionals in primary care. Main body A system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…Appointment availability waiting time and flexibility of PCP’s reception hours were seemingly unimportant to physicians and were only raised in the patients’ focus groups. This supports the recommendation [ 18 , 38 ] to identify attributes for DCE studies within a targeted population. In studies that examine patients’ preferences, in order to better understand patient attributes, it is not enough to conduct a literature review and consult physicians; the patients themselves need to be the main population identifying what is important to them.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Appointment availability waiting time and flexibility of PCP’s reception hours were seemingly unimportant to physicians and were only raised in the patients’ focus groups. This supports the recommendation [ 18 , 38 ] to identify attributes for DCE studies within a targeted population. In studies that examine patients’ preferences, in order to better understand patient attributes, it is not enough to conduct a literature review and consult physicians; the patients themselves need to be the main population identifying what is important to them.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, there are limited studies with validated attributes and levels among targeted populations; and in many studies, the working methods were insufficiently described and reported [ 18 , 19 ]. In addition, the Think Aloud method, which has the potential to deepen our understanding of the attributes and levels that influence patients’ choice, has also received scant research attention [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The discrete choice experiment (DCE) is a commonly used approach for eliciting patient preferences based on random utility theory [10][11][12]. In a DCE, respondents are asked to choose a preferred therapeutic option between two or more alternatives that mimic the real-world choices, described by several attributes and associated levels [11,[13][14][15]. Through the analysis of respondents' discrete choices, a DCE could estimate patients' latent preferences (known as part-worth utilities) associated with the descriptive attributes and their willingness-to-pay (WTP) for changes to the attribute levels [13,16].…”
Section: Key Points For Decision Makersmentioning
confidence: 99%
“…The conditional logit is one of the common estimation models used for statistical analysis [21][22][23][24]. The selection set was estimated by a conditional logit regression model using Stata software.…”
Section: Discussionmentioning
confidence: 99%